Pelatihan Menulis Produk Jurnalistik dan Cerpen di Media Massa - Hasan Busri; Mohamad Badrih; Abdul Rani; Khoirul Muttaqin (BERNAS: Jurnal Pengabdian Kepada Masyarakat, 2023)
This community service with the title "Training on Writing Journalistic Products and Short Stories is a community service carried out by PBSI FKIP Unisma lecturers at MA Al-Maarif Singosari, Malang Regency. This service is carried out by the trainer method, namely there is a process of approach, facility provision, training, and evaluation. This was motivated by the principal's information that said that almost no students wrote in the mass media outside the school. Even though the school is a well-known school in the region and it will be very important to write in the mass media outside the school. The results of the service explained that the students were very enthusiastic in the training. There are two stages of training, namely the delivery of material and the evaluation of written products. The master coffee technique is used in this platihan. It is used to trigger students to be able to write well according to the example of writing by writers who are experts. Students are also able to write by making changes to almost all parts of the modeled. The result of this devotion is that there is a product that deserves to be sent to the mass media by having to go through editing first.